Notification for food servicing using RFID and RF module (vibrating gadget) / Mohamad Fazirul Mohamad Rosali - Mohamad Rosali, Mohamad Fazirul (2013)
Nowadays, RFID technology is rapidly growth and become more complexity. The need of devices reliable and low cost is very necessary. This paper describes project using RFID and RF Module control using the Arduino Uno microcontroller. This project will be commercially uses in public especially in the fast food service system. The main objective of this project is to improve the fast food servicing system and study about RFID and RF module. This project combines of RFID, RF module and vibrate gadget. The card will be handled by worker and the vibrate gadget will be given to co stumer after order and paid for the meal.